Resin Gingival Barrier as a Polymerizable Try-In Paste for Dynamic Try-In of Crowns and Veneers - Abyad, Ahmed; Jarrah, Ziad; Hallak, Amin; Ragab, Hala; Osman, Essam (European Journal of Dentistry, 2020)
Try-in sessions are often performed to check the fit and shape of restorations; however, try-in pastes do not exhibit enough viscosity to keep the restoration in place especially in the case of veneers that keep falling off during try-in. The use of polymerizable soft resins similar to those used as a gingival barrier in bleaching treatment can lock the veneer or crown in place during try-in for dynamic assessment of the restoration, at the same time easy removal of the paste is possible since the resin film is peeled off in one piece leaving no residues for cleanup.
Keywords: ceramics; crowns; veneers; try-in